OBTAINING FLOCCULANTS SERIES-F BASED ON WASTE NITRON FIBER (Scientific journal of the Fergana State University, 2023)
Optimum conditions for obtaining polyelectrolyte-flocculants were determined on the basis of "Nitron" fiber production waste produced in Navoiazot, and their physico-chemical, colloid and flocculation properties were studied. In the article, a certain amount of reagents were selected to obtain 100 grams of F-series flocculant under laboratory conditions. Flocculants named F-1, F-2 and F-3 are obtained by etherification of partially hydrolyzed "Nitron" fiber waste (NFW) with aliphatic alcohols (propyl, pentyl and heptyl) in a mixture of organic solvents in the presence of sulfuric acid (catalyst).